Significantly improved dielectric properties of polylactide nanocomposites via TiO2 decorated carbon nanotubes. (December 2019) - Wu, Wei; Liu, Tao; Zhang, Dongli; Sun, Qijun; Cao, Ke; Zha, Junwei; Lu, Yang; Wang, Bin; Cao, Xianwu; Feng, Yanhong; Roy, Vellaisamy A.L.; Li, Robert K.Y.
Graphical abstract: Highlights: TiO2 coated MWCNTs were synthesized in aqueous solution. The dielectric constant of PLA composite was improved significantly with a low increase in dielectric loss. The thermal stability and storage modulus of PLA were enhanced. Abstract: Titanium dioxide decorated multi-walled carbon nanotubes (MWCNTs@TiO2 ) were fabricated in aqueous solution via a facile sol-gel method. The results of TEM, XRD, XPS and TGA confirmed that TiO2 had been coated on the surface of MWCNTs successfully. The polylactide (PLA) nanocomposites containing various content of MWCNTs@TiO2 were prepared by a solution mixing method, followed by a hot compression process. The results revealed that the introduction of MWCNTs@TiO2 enhanced the thermal stability and crystallinity of PLA without affecting the crystal phase. Moreover, the PLA nanocomposite containing of 5 wt% MWCNTs@TiO2 had a dielectric constant of 26.6, which was 8.3 times higher than that of the pure PLA (3.2), while the dielectric loss still remains at a low value of 0.2 at 1000 Hz. The decorated TiO2 nanoparticles on the surface of MWCNTs could serve as insulating layers to suppress the dielectric loss effectively.